Pengaruh Saintifik Terhadap Pemikiran Cendikiawan Muslim Jawa - Ash Shufiyah, Fathimatuz Zahro' Ash Shufiyah; Noviyanti, Derisma Vita (Postgraduate Studies UIN Sunan Ampel Surabaya, 2024)
The island of Java has long been a central hub for the spread and development of Islam in the Indonesian Archipelago, producing numerous scholars and Muslim intellectuals who have contributed significantly to the advancement of Islamic knowledge and Qur’anic exegesis. Among the Qur’anic commentaries originating from Java, two works stand out for their scientific approach: Tafsir Salman, compiled by the Bandung Institute of Technology (ITB), and Tafsir Ilmi, developed by the Ministry of Religious Affairs of the Republic of Indonesia. Both interpretations employ scientific perspectives to elucidate the verses of the Qur’an, demonstrating that Qur’anic exegesis can adapt to the ongoing development of science and technology. This approach introduces a distinctive nuance compared to traditional exegesis, emphasizing the integration of science and religion. The study of these two tafsirs provides valuable insights into how Indonesia’s Islamic tradition remains open to innovation and highlights the deep interconnection between scientific knowledge and Islamic thought in the modern era.